Innovation in higher education: a study on the perception of students in Ecuador - Rosales Nieto, Darwin Eugenio (2020)
For higher education institutions, innovation becomes a key and consubstantial objective with its activity of training professionals, who provide solutions to society's problems. Universities invest huge resources to achieve their goals in innovation; however, these investments are not always perceived by the student body, which generates feelings of dissatisfaction and lack of commitment. The purpose of this article is to know the perception of those who study in public, cofounded and private universities, in the province of Pichincha, in Ecuador, about the resources made available by their universities, in order to guide public entities on the innovation needs that universities present. For this reason, during the period between March and May 2019, surveys were applied to a sample of 768 university bachelor students, from the province of Pichincha, to evaluate four categories of items, differentiating in the study the perception of students of social and exact sciences, and coming from different types of universities. The results indicate that those who study in public universities have a different perception of those who attend private and cofounded universities and those aspects of infrastructure and teaching related are the most relevant, so it is concluded that it is recommendable to prioritize investment in innovation in the mentioned topics, starting from the type of faculties and universities where the perception is more negative.